The role of SOX2 in small cell lung cancer, lung adenocarcinoma and squamous cell carcinoma of the lung - Karachaliou, Niki (Transl Lung Cancer Res, 2013)
SOX2 is a stem cell transcription factor that plays a crucial role in the regulation of embryonic development. It is one of the genes in a set of factors (Oct4, SOX2, Nanog) that are able to reprogram human somatic cells to pluripotent stem cells. Overexpression of SOX2 has been described in all types of lung cancer tissues, including small cell and squamous cell carcinoma but also adenocarcinoma. An in-depth view of the spectrum of genomic alterations in small cell lung cancer (SCLC) has identified SOX2 as a potential target for therapeutic intervention. Amplification of 3q, the most common genomic aberration in squamous lung cancer, has been demonstrated in the evolution of preinvasive squamous lung cancer and implicates SOX2 as a key target of this dynamic process, making SOX2 and its downstream effector components potential targets for biological therapeutics of squamous carcinomas. SOX2 is expressed in nearly 20% of lung adenocarcinoma and is associated with poor prognosis. SOX2 activity was found to promote squamous identity instead of a loss of cellular differentiation consistent with the role of SOX2 as a “lineage-survival oncogene.” Interestingly, SOX2 transcription factor is the predominant downstream target of EGFR signaling and plays a major role in self-renewal growth and expansion of side population cells. In light of the complex actions of SOX2 in regulating normal and tumor development, the elucidation of SOX2-dependent pathways may identify new therapeutic vulnerabilities in lung cancer and uncover additional common pathways between cancer, normal development, and the maintenance of pluripotency.